+0  
 
+1
71
1
avatar+150 

Given that f(x) is a function such that f(1)=2, f(4)=3, f(7)=4, and f^{-1}(x) is the inverse of f(x), what is f^{-1}(f^{-1}(3))?

xXxTenTacion  Aug 29, 2018
 #1
avatar+90969 
+2

f^{-1}(f^{-1}(3))

 

f-1 (3)  = 4

 

So

 

f-1 ( f-1(3) )  =

 

f-1 ( 4)  =   7

 

 

cool cool cool

CPhill  Aug 29, 2018

24 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.